Problems Asscoaite with total correction for tetralogy of fallot in older patients a comparative study - Khan, Ghufranullah; Hussain, Akhtar; Rehman, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Total correction is the ultimate goal one should strive to achieve in a patient with tetraology of Fallot. Although early total correction in infancy is being advocated in an attempt to avoid late sequelae of cyanosis on the heart, brain and lung, two stage reapir is the preferred alternative with us. We routinely offer total correction to patients who are older than 4 years and prefer to do systemic pulmonary shunts if the patients becomes symptomatic before that age. This together with late referral and ignorance of the general population about their disease, has resulted in older patients coming for total correction. In our experience 30 - 50% of our patient are more than 12 years of age at the time of total correction.